TECHNOLOGICAL, PEDAGOGICAL, AND CONTENT KNOWLEDGE (TPACK) PERCEPTIONS OF JUNIOR HIGH SCHOOL ENGLISH TEACHERS IN SAMARINDA - Rifki Fadila; Didik Sucahyo; Yuni Utami Asih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
Technological Pedagogical Content Knowledge (TPACK) competency is a relevant competency that teachers must have in line with the 4.0 era where technological developments are very necessary. This research aims to find out how Technological Pedagogical Content Knowledge (TPACK) perception of junior high school English Teachers in Samarinda and find out whether there are differences in the TPACK perception on factors of gender, age and teaching experience. The sample of study was 42 teachers who were willing to fill out the questionnaire on the distributed Google Form. The results of this research were that the highest TPACK perception was in the Content Knowledge component at 77.98% and the lowest was in the TPK component at 70.12%. The results of this research show that there are no differences in perception based on gender, age, or teaching experience where the Sig (2-tailed) value is> 0.05 so there is no difference in three factors.